2009
DOI: 10.1007/s11248-009-9339-z
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Cry1Ab protein from genetically modified maize (MON810) in relation to total dietary feed proteins in dairy cow digestion

Abstract: To investigate the relative degradation and fragmentation pattern of the recombinant Cry1Ab protein from genetically modified (GM) maize MON810 throughout the gastrointestinal tract (GIT) of dairy cows, a 25 months GM maize feeding study was conducted on 36 lactating Bavarian Fleckvieh cows allocated into two groups (18 cows per group) fed diets containing either GM maize MON810 or nearly isogenic non-GM maize as the respective diet components. All cows were fed a partial total mixed ration (pTMR). During the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 11 publications
3
55
0
Order By: Relevance
“…Other investigators also found immunoreactive rCry1Ab proteins (or protein fragments) of several sizes in MON810 Bt-maize, including a 34-kD protein (Paul et al, 2010;Grubber et al, 2011). Further, the 34-kD protein apparently has greater stability to proteolysis, which might be relevant for potential effects of GM maize in agroecosystems (Paul et al, 2010). To our knowledge, these peptides have not yet been specifically tested for toxicity to nontarget organisms.…”
Section: Discussionmentioning
confidence: 95%
“…Other investigators also found immunoreactive rCry1Ab proteins (or protein fragments) of several sizes in MON810 Bt-maize, including a 34-kD protein (Paul et al, 2010;Grubber et al, 2011). Further, the 34-kD protein apparently has greater stability to proteolysis, which might be relevant for potential effects of GM maize in agroecosystems (Paul et al, 2010). To our knowledge, these peptides have not yet been specifically tested for toxicity to nontarget organisms.…”
Section: Discussionmentioning
confidence: 95%
“…After feed intake, both the DNA and protein are further degraded within the bovine gastrointestinal tract Wiedemann et al, 2006). Paul et al (2010) reported that the Cry1Ab protein from MON810 is increasingly degraded during digestion in the dairy cow gastrointestinal tract via small fragments, and in comparison with total protein in feed, the relative amount of CrylAb protein in faeces is markedly reduced, indicating that CrylAb protein is not more stable than other proteins in the feed.…”
Section: Discussionmentioning
confidence: 99%
“…Cry proteins are degraded by enzymatic activity in the gastrointestinal tract, meaning that only low amounts of intact Cry proteins would remain in the faeces. This was demonstrated for Cry1Ab (Einspanier et al, 2004;Lutz et al, 2005;Lutz et al, 2006;Wiedemann et al, 2006;Guertler et al, 2008;Paul et al, 2010). Further degradation of the protein in manure and faeces will take place because of microbiological proteolytic activity.…”
Section: Interactions Of the Gm Plant With Non-target Organisms 34mentioning
confidence: 91%